An empirical investigation of the link between market share and valuation of earnings and growth opportunities. (25th April 2011) - Swirsky, Steven; Islam, Mazhar M.
This study investigates the effect of changes in firm's market share on market valuation of earnings and growth opportunities during the period preceding the 2001 recession. The historical time horizon was selected to avoid bias caused by changes in market/economic conditions. Multiple regression models have been used to test different hypotheses contained in this study. Empirical results indicate that the link between current performance and future performance is significantly enhanced in the presence of market share gains. Furthermore, the relation holds for up to three years into the future after introducing other measures that represent the markets' beliefs about future growth prospects. In addition, the results support that the market incrementally prices the earnings of firms that are increasing market share when the market perceives future growth opportunities to be greater relative to when growth opportunities are perceived to be fewer. Future research is invited to extend this work into the current US recession.